Carbapenemase-producing Enterobacteriaceae in Europe: a survey among national experts from 39 countries, February 2013 - C Glasner; B Albiger; G Buist; A Tambić Andrašević; *The European Survey on Carbapenemase-Producing Enterobacteriaceae (EuSCAPE) working group; Ana Kaftandzieva (My University, 2013)
The spread of carbapenemase-producing Enterobacteriaceae (CPE) is a threat to healthcare delivery, although its extent differs substantially from country to country. In February 2013, national experts from 39 European countries were invited to self-assess the current epidemiological situation of CPE in their country. Information about national management of CPE was also reported. The results highlight the urgent need for a coordinated European effort on early diagnosis, active surveillance, and guidance on infection control measures.